Pengaruh Pernikahan di Bawah Umur Terhadap Tingkat Perceraian di Pengadilan Agama Purworejo - Widiyanto, Hari; Muhajir; Lunaraisah; Az Zahra Jasmine Yustisio (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Underage marriage takes place at an age below the productive age, which is less than 20 years for women and less than 25 years for men. Therefore, the problem in this study is what factors influence the occurrence of underage marriage, and how underage marriage affects the divorce rate, especially in the Purworejo District Court area. This study aims to determine the causes, impacts, or influences of underage marriage in Purworejo Regency and also to educate the public about the influence, causes, and impacts of underage marriage. This study uses a qualitative approach method that is empirical. Cases of underage marriage in Purworejo Regency increase and decrease every year, cases of underage marriage are caused by several factors including economic, environmental, and parental factors. This study can conclude that underage marriage is more likely to end in divorce because many are not ready to face emotional, physical, financial, and other needs to fulfill life after marriage and many risks and losses arise from underage or underage marriage, both through personal and social environmental impacts.